Preparation of collagen modified photopolymers: a new type of biodegradable gel for cell growth - KAHRAMAN, MEMET VEZİR; KAYAMAN APOHAN, NİLHAN (SPRINGER, 2010)
In this study a new branched methacrylated poly(propylene glycol-co-lactic acid) (PPG-PLA-IEM) and methacrylated cellulose acetate butyrate resin (CAB-IEM) were synthesized. Hydrogels with various amounts of PPG-PLA-IEM and CAB-IEM (25, 50 and 75 wt% IEM modified) were prepared by photopolymerization. Collagen tethered PEG-monoacrylate (PEGMA-collagen) was prepared and introduced as a bioactive moiety to modify the hydrogel in order to enhance cell affinity. In vitro attachment and growth of 3T3 mouse fibroblasts and human umbilical vein endothelial cells (HUVEC) on the hydrogels with and without collagen were also investigated. It was observed that, the collagen improves the cell adhesion onto the hydrogel surface. With the increasing amount of collagen, cell viability increased by 28% for ECV304 (P < 0.05) and 30% for 3T3 (P < 0.05).
Keywords: CELLULOSE-ACETATE BUTYRATE; STROMAL CELLS; SCAFFOLDS; BONE; HYDROGELS; BEHAVIOR; DIFFERENTIATION; CYTOTOXICITY; METHACRYLATE; DEGRADATION